2007
DOI: 10.1111/j.1365-246x.2007.03432.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmixing magnetic remanence curves withouta prioriknowledge

Abstract: S U M M A R YMany of the natural materials studied in rock and environmental magnetism contain a mixed assemblage of mineral grains with a variety of different origins. Mathematical decomposition of the bulk magnetic mineral assemblage into populations with different properties can therefore be a source of useful environmental information. Previous investigations have shown that such unmixing into component parts can provide insights concerning source materials, transport processes, diagenetic alteration, auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 52 publications
1
106
0
Order By: Relevance
“…In natural sediments, several magnetic components of different sources are generally mixed, and it is often diffi cult to characterize individual components; therefore, unmixing of magnetic components has been an issue in environmental magnetic studies (e.g., Egli, 2004a;Heslop and Dillon, 2007;Watkins et al, 2007;Lascu et al, 2010). Egli (2004b) demonstrated that rock magnetic parameters, including the ratio of anhysteretic remanent magnetization susceptibility to saturation isothermal remanent magnetization (k ARM / SIRM), and the coercivity distribution of ARM and IRM, are quite useful for unmixing and characterizing magnetic mineral assemblages in sediments; he identifi ed two magnetically distinct groups of biogenic magnetite, biogenic soft (BS) and biogenic hard (BH), that probably correspond to different magnetosome morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In natural sediments, several magnetic components of different sources are generally mixed, and it is often diffi cult to characterize individual components; therefore, unmixing of magnetic components has been an issue in environmental magnetic studies (e.g., Egli, 2004a;Heslop and Dillon, 2007;Watkins et al, 2007;Lascu et al, 2010). Egli (2004b) demonstrated that rock magnetic parameters, including the ratio of anhysteretic remanent magnetization susceptibility to saturation isothermal remanent magnetization (k ARM / SIRM), and the coercivity distribution of ARM and IRM, are quite useful for unmixing and characterizing magnetic mineral assemblages in sediments; he identifi ed two magnetically distinct groups of biogenic magnetite, biogenic soft (BS) and biogenic hard (BH), that probably correspond to different magnetosome morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Remanence acquisition or demagnetization curves and fielddependence of induced magnetization probed through hysteresis loops and first-order reversal curve (FORC) distributions are the dominant magnetic data currently being numerically unmixed to characterize the magnetic mineral components (Robertson and France, 1994;Carter-Stiglitz et al, 2001;Egli, 2003Egli, , 2013Fabian, 2003;Heslop and Dillon, 2007;Lascu et al, 2010Lascu et al, , 2015Heslop, 2015;Church et al, 2016;Fabian et al, 2016;Maxbauer et al, 2016b;Zhang et al, 2016). While important and useful results have emerged, the currently applied methods present important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis needs further rock magnetic work to confirm. Nie et al (2014c) recently performed backfield remanence curve unmixing on loess and red-clay using the method developed by Heslop and Dillon (2007), which does not require pre-defined end members. The results reveal that backfield curves of both loess and red-clay can be unmixed as two end members (Figure 10).…”
Section: Comparing Other Magnetic Parameters Between the Loess-paleosmentioning
confidence: 99%